Simulation Analysis of Magnetic Gradient Full-Tensor Measurement System. (20th March 2021) - Xu, Lei; Zhang, Ning; Fang, Liqing; Chen, Huadong; Lin, Pengfei; Lin, Chunsheng
Abstract : The magnetic gradient full-tensor measurement system is diverse, and the magnetometer array structure is complex. Aimed at the problem, seven magnetic gradient full-tensor measurement system models are studied in detail. The full-tensor measurement theories of the tensor measurement arrays are analyzed. Under the same baseline distance, the magnetic dipole model is used to simulate the measurement system. Based on different measurement systems, the paper quantitatively compares and analyzes the error of the structure. A more optimized magnetic gradient full-tensor measurement system is suggested. The simulation results show that the measurement accuracy of the planar measurement system is slightly higher than that of the stereo measurement system. Among them, the cross-shaped and square measurement systems have relatively smaller structural errors and higher measurement accuracy.